(untitled) (Revista de Ingeniería Industrial y Mecánica, 2018)
Las actuales prácticas de paletización desarrolladas por los ingenieros en empaque sugieren una importante incidencia de los softwares de simulación en problemas de paletizado (PLP). Las actuales tomas de decisión en este campo se orientan hacia una logística ajustada mediante el respaldo de herramientas informáticas robustas. Abstract: The current palletization practices developed by packaging engineers suggest an important incidence of simulation software in palletizing problems (PLP). The current decision-making in this field is oriented towards an adjusted logistics through the support of robust computer tools. In this sense, we analyze two programs of extended professional use and different business profile under quality and performance standards: TOPS Pro (payment) and PLMPack Stack Builder (free and open source). Through the significance of their contributions and considering the preferences collected and analyzed on a group of professionals in the area, an executable script is developed in the "R" environment, which guarantees a robust and reliable knowledge on the efficiencies of load distributions. In palletizing processes, for decision making in PLP. In this article we expose the distributions of load distinguished in palletizing processes corroborated by three routes: current standards, risk analysis according to professional expertise and computer calculation of spatial efficiency, Finally we showthe outputs of the package prepared and available for growth in "R”. We consider that the methodology used to detect relevant factors in the current programs by generating new open codes, is a sample of the possible informatic empowerment in various fields of engineering. Keywords: lean palletizing; palletization risks; load distributions; palletizing in R.